Стандартизация гуминовых кислот низинного древесно-травяного вида торфа Томской области - Зыкова М. В.; Белоусов М. В. Михаил Валерьевич; Гурьев А. М.; Ахмеджанов Р. Р. Рафик Равильевич; Юсубов М. С. Мехман Сулейман-оглы (Сулейманович) (2013, 2013)
Заглавие с экрана